The Reciprocal Acculturation of Islamic Culture and Local Culture in the Nusantara: A Historical Review - Abdullah, Anzar; Muhammad Asdam; Alimbagu, Andi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article investigates the process of acculturation between Islam and local cultures in the Indonesian archipelago (Nusantara) from the 13th to the 17th century. Employing historical and cultural approaches, the study is grounded in the theories of cultural acculturation, diffusion, Islamic indigenization, and symbolic interactionism. The objective is to demonstrate that Islam did not arrive as a hegemonic or coercive force, but rather integrated harmoniously with existing cultural traditions. By examining the roles of trade, art, governance, and religious rituals, the article highlights how Islam engaged in constructive and adaptive dialogue with indigenous practices. The findings suggest that the emergence of Islam in Indonesia was marked by a creative and dynamic process of cultural negotiation, ultimately contributing to the development of a moderate and tolerant Islamic identity.